Avoiding trivia the role of strategic planning in American foreign policy - Drezner, Daniel W. (Brookings Institution Press, 2009)
"Critically assesses the past, future, and potential future role and impact of long-term strategic planning in foreign policy. Key figures from past decades of foreign policy and planning provide authoritative insight on the difficulties and importance of thinking and acting in a coherent way for the long term"--Provided by publisher.